Propuesta de mejoramiento a las actividades del sistema de gestión de seguridad y salud en el trabajo para la distribuidora Tunja Boyacá de la empresa AVSA S.A. (2023)
In this work, a diagnosis is made of compliance with the Occupational Safety and Health Management System (OSH) in the company AVSA S.A in the department of Boyacá, specifically with regard to accident control and prevention, occupational incidents and diseases. In addition, a training plan is proposed that includes all the risks related to the tasks performed by the Collaborators in their daily routine, with the aim of consolidating knowledge in the prevention of risks related to such hazards.